The new European Parliament? The Common Agricultural Policy under codecision after the Lisbon Treaty - Freitas, Luís Sargento (2018)
This research intends to analyze the impacts of codecision between the main three legislative institutions (Commission, Council of the EU and European Parliament [EP]) in the outcomes of legislation, how codecision developed through the years and how members of the European Parliament (MEP’s) have addressed these issues, particularly regarding the Common Agricultural Policy (CAP), in their plenary speeches. We chose the CAP as subject matter as it is the most expensive policy in the EU budget and one of the oldest common policies in the history of European integration, having for 50 years been decided merely between the Council of Ministers and the European Commission (and only after 2009 with the EP under the codecision system). Codecision was also chosen as it was the decisive factor that allowed the EP to no longer remain just an advisory institution with limited powers as it was before 1991. Codecision has been decisive, insofar as it has changed the nature of EU legislation particularly after the Lisbon treaty where it reaches 84 EU policy areas. The literature in this field has yet to provide enough evidence on the results of the impact of codecision and the role of the newly empowered post-Lisbon EP (which has since possessed equal powers to the other two legislative institutions). This study intends to address these issues with a comparative analysis on a number of plenary speeches by MEPs and presidents of the EP in the seventh legislature of the EP (2009- 2014). Only then can we clearly state what codecision did, in fact, change in the CAP and in the EU in general and how the MEPs have observed/debated these developments. The Lisbon treaty was a decisive and very important development of European integration and the parliamentarization of the EU in recent years as it endowed the EP with 46 new areas that are now decided under codecision (85 in total). However, one can also state that the other two legislative institutions have tried to circumvent the role of the EP and that the financial and economic circumstances of the eurozone crisis diminished the role of this institution. The speeches of the MEPs and the Presidents of the EP that I analyze in this study clearly state that these events and concerns are true.